PTH1R-CaSR Cross Talk: New Treatment Options for Breast Cancer Osteolytic Bone Metastases - Yanmei Yang; Bin Wang (International Journal of Endocrinology)
Metastatic breast cancer (BrCa) is currently incurable despite great improvements in treatment of primary BrCa. The incidence of skeletal metastases in advanced BrCa occurs up to 70%. Recent findings have established that the distribution of BrCa metastases to the skeleton is not a random process but due to the favorable microenvironment for tumor invasion and growth. The complex interplay among BrCa cells, stromal/osteoblastic cells, and osteoclasts in the osseous microenvironment creates a bone-tumor vicious cycle (a feed-forward loop) that results in excessive bone destruction and progressive tumor growth. Both the type 1 PTH receptor (PTH1R) and extracellular calcium-sensing receptor (CaSR) participate in the vicious cycle and influence the skeletal metastatic niche. Thus, this review focuses on how the PTH1R and CaSR signaling pathways interact and contribute to the pathogenesis of BrCa bone metastases. The effects of intermittent PTH and allosteric modulators of CaSR for the use of bone-anabolic agents and prevention of BrCa bone metastases constitute a proof of principle for therapeutic consideration. Understanding the interplay between PTH1R and CaSR signaling in the development of BrCa bone metastases could lead to a novel therapeutic approach to control both osteolysis and tumor burden in the bone.